A nova retórica e a perspectiva dialogal nas redações do Enem - Silva, Ana Gabriela Moreira e (2020)
The National High School Exam (Enem) has great relevance in the Brazilian scenario as it is the main means of access to universities. Given its importance, each year, as tests that become more complex and discussed by specialists in each of the areas of concentration of the exam. Such importance and attention given to Enem are many researchers who research on subjects to develop scientific research, mainly with regard to the exam writing test, which is the focus of this research. Therefore, this dissertation, entitled The new rhetoric and the dialogical perspective in Enem newsrooms, has as its object of analysis Enem newsrooms that get maximum marks in the period between the years 2015 to 2018, as well as the writing excerpts that were installed in the situation 'hurt human rights' in the same period, from 2015 to 2018. This is the case of an analysis of this corpus in the fundamentals, mainly in the Argumentation studies, more precisely, in the theory of the universal auditorium of Chaïm Perelman and Olbrechts- Tyteca (1996), in Christian Plantin's notion of interaction and argumentative argument. Discourse analysis, by Ruth Amossy (2016), will also be considered, as well as Bakhtin's (2009) notion of dialogue. In addition to these theorists, other references used, such as Aristotle and Goffman (2014), for example. Furthermore, the theoretical framework will be the basis for the analysis of the corpus, to demonstrate how the examination, without the context of Enem's wording, creates an image of its auditorium and writes its text based on the influence of the dissemination of the thousand note essays in the Enem Participant Primer. The second moment of the exhibition analysis, based on an execution that fits the situation 'hurt human rights', how an interaction occurs between the exam and the examining board at the time of the production and evaluation of the written essay, and how it materializes an interruption of argumentative stasis. For these two moments of analysis, in this qualitative quality research, the top and doxai concepts are used mainly, which, in general, refer to socially accepted opinions and the values that permeate society, respectively. With the analysis path, the role of the examining board was observed within the argumentative character of the Enem newsroom.